A case of squamous cell carcinoma in an ewe - Imad Ibrahim Ali Al-Sultan; Mohd Azam Khan Goriman Khan; Jasni Sabri; Abd Rahman Aziz (Design for Scientific Renaissance, 2013)
Squamous cell carcinoma is a tumour frequently found to occur in the reproductive tract of sheep. This report describes the gross and histopathological characteristics of squamous cell carcinoma on the head of an ewe. A sheep with a large mass of 9 X 15cm on the right lateral frontal region of the head was submitted for post mortem. Necropsy examination revealed a firm, black lump with multiple cavitations containing whitish pus. The neoplastic mass infiltrated and extended, completely covered the right eye. Other adjacent structures appeared normal. Histopathological examination showed typical neoplastic squamous epithelial cells arranged as islands and cords invading the basal membrane and dermis from the epidermis. There were focal areas of necrosis, frequent and massive keratinisation and pronounced infiltration of inflammatory cells predominantly mononuclear’s. This paper reports a well differentiated malignancy of skin squamous epithelial/epidermal cells forming a carcinomatous mass at a site of the head with abscess of skin not previously reported in ewe.